Metodologías activas aplicadas en el proceso de enseñanza-aprendizaje del subnivel superior de Educación General Básica del Colegio de Bachillerato Beatriz Cueva de Ayora en el año lectivo 2023-2024. - Cabrera Cango, Jonathan Rolando (2024)
Active methodologies are teaching strategies that encourage the active participation of students, the development of autonomy in the construction of their own knowledge and promote the acquisition of fundamental social skills for the development of the teaching-learning process, necessary to obtain significant learning in students. That is why, the main objective of the following curricular integration work is to analyze the active methodologies applied in the teaching-learning process of the superior sublevel of Basic General Education of the Beatriz Cueva de Ayora High School in the 2023-2024 school year; The research method is deductive in nature, with a quantitative approach with an exploratory-descriptive scope. Data collection was carried out through the adaptation of a structured questionnaire based on active methodologies applied to the teaching-learning process, Likewise, the population is made up of 15 teachers from the educational institution. To obtain data, a questionnaire was applied with questions based on the Likert and dichotomous scale. Finally, it can be mentioned that the teachers of the educational institution mostly use Project-Based Learning, mentioning that an essential activity in the development of the educational process is the implementation of educational projects aimed at students. Keywords: Teaching-learning, active methodology, interdisciplinarity, problem resolution.